Inactivation of colicin Y by intramembrane helix-helix interaction with its immunity protein - Smajs, David; Dolezalová, Magda; Macek, Pavel; Zídek, Lukás (The FEBS journal, 2008)
The construction of hybrids between colicins U and Y and the mutagenesis of the colicin Y gene (cya) have revealed amino acid residues important for interactions between colicin Y and its cognate immunity protein (Cyi). Four such residues (I578, T582, Y586 and V590) were found in helices 8 and 9 of the colicin Y pore-forming domain. To verify the importance of these residues, the corresponding amino acids in the colicin B protein were mutated to the residues present in colicin Y. An Escherichia coli strain with cloned colicin Y immunity gene (cyi) inactivated this mutant, but not the wild-type colicin B. In addition, interacting amino acid pairs in Cya and Cyi were identified using a set of Cyi point mutant strains. These data are consistent with antiparallel helix-helix interactions between Cyi helix T3 and Cya helix 8 of the pore-forming domain as a molecular mechanism of colicin Y inactivation by its immunity protein.
Keywords: sekundární struktura proteinů; Colicins; Escherichia coli K12; Immunity; koliciny; imunita; Protein Structure, Secondary; proteiny z Escherichia coli; Binding Sites; Protein Binding; vazebná místa; vazba proteinů; Escherichia coli Proteins